Experiment on the Production of Soft Cookies with the Addition of Black Glutinous Rice Flour: an Organoleptic, Physical, and Chemical Test - Bunga Pertiwi; Octavianti Paramita (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study was motivated by the suboptimal utilization of black glutinous rice flour as a local food ingredient in the development of modern products. The study aimed to develop and analyze the quality of soft cookies using black glutinous rice flour as a substitute for wheat flour. The study employed an experimental design with four treatments: 0%, 25%, 50%, and 100% black glutinous rice flour. The testing included organoleptic tests by untrained panelists, sensory tests by three trained panelists of a descriptive nature, as well as physical and chemical tests. The results showed significant differences in preference tests regarding color, aroma, taste, texture, and overall quality. However, the sensory tests did not reveal significant differences among the treatments. The protein content in all treatments met SNI standards and did not differ significantly, while physical quality showed a change in color as the proportion of black glutinous rice flour increased. This study concludes that black glutinous rice flour has the potential to serve as a wheat flour substitute in the production of soft cookies that are sensorially acceptable and supports the development of nutritious local foods